“Opening Our Time Capsule”—Creating an Individualized Music and Other Memory Cues Database to Promote Communication Between Spouses and People With Dementia During Visits to a Nursing Home - Dassa, Ayelet (Frontiers in Medicine, 2018)
Background Family members play a critical role in caring for people with dementia, and their involvement in care continues even after their loved ones are placed in long-term care facilities. The dynamics of family involvement following institutionalization are complex and challenging. The strain on caregivers does not cease and communication difficulties are a major barrier due to deteriorating language abilities as a result of dementia. Also, caregivers’ involvement has implications on the quality of life of both the elderly and his family members. Objective To help alleviate caregivers’ burden during visiting hours, by promoting communication opportunities. The program included the creation of an individualized database using personal music and photos that present life episodes. Method A pilot study explored spouses’ experience during visits and the process of creating and using the individualized database. Participants included three women who regularly visited their partners who had dementia and resided in a nursing home. The first phase included creating an individualized database for each couple. In the second phase, four meetings were conducted, each woman with her partner, utilizing the database on a tablet. A qualitative research case study design was used and various types of data were collected and analyzed. The data included interview reports (pre-post intervention), preparation meetings reports, spouses’ recorded reactions at the end of each of the four visits, and the music therapist’s written log during the program. Results All documented data revealed the difficulties, mostly the communication barrier, encountered by the three women during their visits to the nursing home. All reported that using the individualized database helped them to find ways to communicate with their partners, relive shared past experiences, and alleviate the stress and feelings of disconnection during visits. Conclusion Forming a bridge between past and present via individualized music and photos databases can be helpful in bridging the gap between people with dementia in nursing homes and their family members.